Dignity According to the Subject. Three Possible Meanings in Conventionality Control - Lell, Helga María (2021)
This paper presents three categories in which the notion of dignity can be used in jurisprudence, depending on the subject to which it is ascribed: as institutional status, as a characteristic of the human being and as a characterization of other elements. In each one of the types, in the first place, a theoretical explanation is made that, although brief, tries to introduce some characteristics about the respective meaning. Second, it describes how the Inter-American Court of Human Rights has used the term «dignity» in the respective sense; that is, a review of the casuistry is included. Finally, some ideas are discussed. The methodology has been analytical regarding the use of the concept and is based on an analysis of the contentious cases and theadvisory opinions of the mentioned institution.